Krishna
0

Step 1: Before going to do the problem, Find the knowns and unknowns in and note it down.


Step 2: Explore the given rule

              EXAMPLE: x_{n+1} = ax_n - 3

                                Succeeding term = a (preceding term) - 3


Step 3: By using the given rule find the required term (x_2, x_3,x_4...etc)

            NOTE: According to the given rule substitute the values to get the required

                        term.

            EXAMPLE: For an attempt to  find the x_3

                                x_{n+1} = ax_n - 3

                                      x_3 =  ax_2 - 3

                            Substitute the values x_2 (calculate it otherwise they will mention in the question x_2 = a - 3)

                                x_ 3 = a(a - 3) - 3

                                  x_3 = a^2 – 3a – 3

Step 4: Equate the given term value to the term calculated by the rule (both represents the same value, so we can equate them)

            EXAMPLE : a^2 – 3a – 3 = 7


Step 5 : Simplify the quadratic equation to find the requires value(a)

            NOTE: Use the Factorization method  

(Answer: a = 5 or – 2)